1992
DOI: 10.1021/jm00087a010
|View full text |Cite
|
Sign up to set email alerts
|

A new class of bradykinin antagonists: synthesis and in vitro activity of bissuccinimidoalkane peptide dimers

Abstract: A systematic study on the dimerization of the bradykinin (BK) antagonist D-Arg0-Arg1-Pro2-Hyp3-Gly4-Phe5-Ser6-D-Phe 7-Leu8-Arg9 has been performed. The first part of this study involved compounds wherein dimerization was carried out by sequentially replacing each amino acid with cysteine and cross-linking with bismaleimidohexane. The second part of this study utilized a series of bissuccinimidoalkane dimers wherein the intervening methylene chain was varied systematically from n = 2 to n = 12 while the point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 3 publications
1
53
0
Order By: Relevance
“…However, the mode of bridging can play a critical role, as recently reported by Cheronis et al [43] for bradykinin dimers and, as well documented in the present study, for the hormone gastrin even in terms of conformational space. The identical rationale can be applied to the design and expression of ef- ficient conformational epitopes.…”
Section: Resultssupporting
confidence: 85%
“…However, the mode of bridging can play a critical role, as recently reported by Cheronis et al [43] for bradykinin dimers and, as well documented in the present study, for the hormone gastrin even in terms of conformational space. The identical rationale can be applied to the design and expression of ef- ficient conformational epitopes.…”
Section: Resultssupporting
confidence: 85%
“…The syntheses, performed by conventional solution methods [10], were not described in detail. More recently, Cheronis et al [11] described bradykinin antagonist homo-and hetero-dimers obtained using bissuccinimidoalkane cross-linkers for the selective ligation of cysteine residues included in the sequence of the monomeric peptide. Once again, the dimerization reaction was performed in solution.…”
Section: Synthesismentioning
confidence: 99%
“…The increase in potency and duration of action of CP 0127 is the result of bivalent binding cooperation and dimerization of bradykinin at position 6 with cystein [11]. Given as an intravenous bolus injection in order to measure its ability of blocking bradykinin-induced (bolus injections, intra-arterially) hypotension in the rat, the pharmacodynamic half-life of CP 0127 is approximately 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…After termination of a continuous CP 0127 infusion its duration of action is roughly of the same magnitude in the rat and rabbit [personal communication from J.C. Cheronis, Cortech Inc.]. Recent in vitro studies have shown that CP 0127 is a potent inhibitor of bradykinin-induced smooth cell contraction in guineapig ileum and in rat uterus preparations, known to contain B2-type receptors [11]. Moreover, CP 0127 reversed lipopolysaccharide-induced hypotension in anaesthesized rats and prevent death in rats and in rabbits given lethal doses of Escherichia coli endotoxin [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation